The Genus Alternanthera: Phytochemical and Ethnopharmacological Perspectives - Singla, Rajeev K.; Dhir, Vivek; Madaan, Reecha; Kumar, Deepak; Singh Bola, Simranjit; Bansal, Monika; Kumar, Suresh; Dubey, Ankit Kumar; Singla, Shailja; Shen, Bairong (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: The genus Alternanthera (Amaranthaceae) comprises 139 species including 16 species used traditionally for the treatment of various ailments such as hypertension, pain, inflammation, diabetes, cancer, microbial and mental disorders. Aim of the review: To search research gaps through critical assessment of pharmacological activities not performed to validate traditional claims of various species of Alternanthera. This review will aid natural product researchers in identifying Alternanthera species with therapeutic potential for future investigation. Materials and methods: Scattered raw data on ethnopharmacological, morphological, phytochemical, pharmacological, toxicological, and clinical studies of various species of the genus Alternanthera have been compiled utilizing search engines like SciFinder, Google Scholar, PubMed, Science Direct, and Open J-Gate for 100 years up to April 2021. Results: Few species of Alternanthera genus have been exhaustively investigated phytochemically, and about 129 chemical constituents related to different classes such as flavonoids, steroids, saponins, alkaloids, triterpenoids, glycosides, and phenolic compounds have been isolated from 9 species. Anticancer, antioxidant, antibacterial, CNS depressive, antidiabetic, analgesic, anti-inflammatory, and immunomodulator effects have been explored in the twelve species of the genus. A toxicity study has been conducted on 3 species and a clinical study on 2 species. Conclusions: The available literature on pharmacological studies of Alternanthera species reveals that few species have been selected based on ethnobotanical surveys for scientific validation of their traditional claims. But most of these studies have been conducted on uncharacterized and non-standardized crude extracts. A roadmap of research needs to be developed for the isolation of new bioactive compounds from Alternanthera species, which can emerge out as clinically potential medicines.